PERANAN KEMAMPUAN VERBAL DAN KEMAMPUAN NUMERIK TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA - Ari Irawan; Gita Kencanawaty (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
The purpose of this study to see the effect of verbal and numerical skills on critical thinking skills of mathematics, verbal ability to influence critical thinking skills of mathematics, numerical ability to influence critical thinking ability in mathematics. The method used is a survey where given a test of verbal ability, numerical kemamuan math and critical thinking skills. This research sample MIA class XI students in high schools in the city of Depok representing each district taken as many as 9 schools with a total sample of 360 respondents. Hypothesis testing using two-way ANOVA. Results of the study showed there are significant verbal and numerical ability jointly to the critical thinking skills of mathematics, there is the influence of the verbal skills of critical thinking skills matametika, there is the influence of numerical ability of the critical thinking skills of mathematics.